2019
DOI: 10.1172/jci.insight.131733
|View full text |Cite
|
Sign up to set email alerts
|

L-Citrulline increases nitric oxide and improves control in obese asthmatics

Abstract: BACKGROUND. The airways of obese asthmatics have been shown to be NO deficient, and this contributes to airway dysfunction and reduced response to inhaled corticosteroids. In cultured airway epithelial cells, L-citrulline, a precursor of L-arginine recycling and NO formation, has been shown to prevent asymmetric dimethyl arginine-mediated (ADMA-mediated) NO synthase (NOS2) uncoupling, restoring NO and reducing oxidative stress. METHODS.In a proof-of-concept, open-label pilot study in which participants were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 43 publications
3
55
0
Order By: Relevance
“…assembled asthma cohort [61]. By matching the enzymes of the differential metabolites and the proteins in the PPI network, we found 3 key metabolites: arachidonate, L-arginine, and Lcitrulline.…”
Section: Plos Biologymentioning
confidence: 99%
“…assembled asthma cohort [61]. By matching the enzymes of the differential metabolites and the proteins in the PPI network, we found 3 key metabolites: arachidonate, L-arginine, and Lcitrulline.…”
Section: Plos Biologymentioning
confidence: 99%
“…A recent clinical trial of l-citrulline supplementation in individuals with asthma found that l-citrulline increased FeNO and modestly improved forced expiratory volume in 1 second (FEV 1 ), especially in females with late-onset asthma (17). We and others have found in murine models that manipulation of l-arginine content in the airway compartment via l-arginine treatment or inhibition of the arginase enzyme decreases airway inflammatory cell counts, lung lavage cytokine levels, airways hyperresponsiveness, and arginase activity (18)(19)(20).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…L-arginine and L-citrulline were decreased in the sera of COVID-19 patients ( 50 ). A previous study showed that these metabolites were also decreased in asthma patients ( 49 ). Arachidonate, the precursor of a variety of products that regulate inflammatory pathways ( 51 ), was found to have an increased level in the inflamed airways of asthmatics ( 52 ).…”
Section: Resultsmentioning
confidence: 90%
“…The unique plasma metabolome of asthmatics versus healthy controls also suggests activated inflammatory and immune pathways ( 48 ). Therefore, in addition to PPIs, we also integrated metabolomics data generated in a previously assembled asthma cohort ( 49 ). By matching the enzymes of the differential metabolites and the proteins in the PPI network, we found three key metabolites, including arachidonate, L-arginine, and L-citrulline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation